Pattern Recognition 36th German Conference, GCPR 2014, Münster, Germany, September 2-5, 2014, Proceedings - Jiang, Xiaoyi; Hornegger, Joachim; Koch, Reinhard (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2014)
This book constitutes the refereed proceedings of the 36th German Conference on Pattern Recognition, GCPR 2014, held in Münster, Germany, in September 2014. The 58 revised full papers and 8 short papers were carefully reviewed and selected from 153 submissions. The papers are organized in topical sections on variational models for depth and flow, reconstruction, bio-informatics, deep learning and segmentation, feature computation, video interpretation, segmentation and labeling, image processing and analysis, human pose and people tracking, interpolation and inpainting.